Designing materials with living organisms for care-based practices: An analysis of case studies within the wearables domain - Guarino, Nicla; Ferraro, Venere; Rognoli, Valentina (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
The unsustainable patterns of human consumption, exacerbated by materialism, digital technologies, disruptive global events and the mounting issue of e-waste, demand a fundamental shift in design approaches. In light of these challenges, this paper discusses how integrating living organisms into materials design can facilitate this transition, fostering innovative interactions and enabling care-based practices. By analysing three case studies in interaction design, the research highlights the transformative potential of incorporating biological matter like plants, moulds, bacteria and fungi into domains such as the one of wearables. The biodesign processes examined reveal commonalities, including the unpredictable, transient and time-consuming nature of designing with living organisms, as well as the evolving commitment and sensitivity of both designers and users towards the artefacts. The findings suggest that embracing non-human agency in the design field can nurture empathy and symbiosis and encourage users’ ethical practices, responsibility, and emotional awareness. The study provides valuable insights into embedding care in design, redirecting the focus away from the traditional environmental products’ durability to a designed temporality, capable of engendering long-term emotional durability.